ä»¥é©¬å†…åˆ©ä¸ä¸“äºŒæ ¡æ±‰è¯æ•™æç ”ç©¶åˆ†æž - Derianto, Derianto; Ina, Ina; Suhardi, Suhardi (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2024)
The teachers, modules, and the students are three important learning characteristica. Modules are the materials for learning and guidance to the students and can add to the students' knowledge which can be in the form of writing, sound, things based on definite scientific aspects and put together into a book. Choosing the suitable module that suits the students is one of the significant responsibilities of the teachers. It is because the selected module can affect the entire learning process."Mandarin Languange Module Of Kristen Immanuel II Sungai Raya Vocational School" is a module that comes from various teaching materials and is collected by local teachers which is compiled into a book, and which is classified as a self-made module. In this thesis through, literacy collection and module content analysis, the strengths and the weaknesses have been understood and identified. Through research and analysis, the author concluded "Mandarin Languange Module Of Kristen Immanuel II Sungai Raya Vocational School" is a module that is not yet fulfilled the provisions, even though in terms of suitability aspects, it is already good. However, in the scientific aspects, use and interest are still not according to the rules. Therefore, the author provided several suggestions for module improvement.